Testando a existência de Prêmio de Volatilidade em Ações Líquidas da Bovespa - Cunha, João Marco Braga da (2008)
The existence and the sign of the volatility premium has been causing controversies in the specialized literature. This work proposed, criticized and applied a novel methodology, aiming to test statistically the existence of a premium for volatility, with the advantages of testing for a set of equities jointly, not for individual series, and independent of any specific functional form for the relationship between the expected return and volatility. The results obtained on the application with a set of selected equities from Bovespa were favorable to the existence of the premium.